Haemoglobin levels in patients with Oral Submucous Fibrosis - Lavina Taneja; Bagewadi Anjana; Keluskar Vaishali (Wolters Kluwer Medknow Publications, 2007)
Objectives: To assess the haemoglobin level in patients with Oral Submucous Fibrosis and compare it with healthy subjects. Material & Methods: Patients reporting to Dept. of Oral Medicine, Diagnosis and Radiology KLES's Institute of Dental Sciences, Belgaum, who were clinically diagnosed as Oral Submucous Fibrosis were subjected to haemoglobin level estimation by using Sahli's method. This was compared to age and sex matched subjects. Result: Haemoglobin levels were low in patients with Oral Submucous Fibrosis compared to control, suggestive of anemia in these patients.